Prolonged patient emergence time among clinical anesthesia resident trainees - L McLean House; Nathan H Calloway; Warren S Sandberg; Jesse M Ehrenfeld (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Emergence time, or the duration between incision closure and extubation, is costly nonoperative time. Efforts to improve operating room efficiency and identify trainee progress make such time intervals of interest. We sought to calculate the incidence of prolonged emergence (i.e., >15 min) for patients under the care of clinical anesthesia (CA) residents. We also sought to identify factors from resident training, medical history, anesthetic use, and anesthesia staffing, which affect emergence. Material and Methods: In this single-center, historical cohort study, perioperative information management systems provided data for surgical cases under resident care at a tertiary care center in the United States from 2006 to 2008. Using multiple logistic regression, the effects of variables on emergence was analyzed. Results: Of 7687 cases under the care of 27 residents, the incidence of prolonged emergence was 13.9%. Emergence prolongation decreased by month in training for 1st-year (CA-1) residents (r2 = 0.7, P< 0.001), but not for CA-2 and CA-3 residents. Mean patient emergence time differed among 27 residents (P < 0.01 for 58.4% or 205/351 paired comparisons). In a model restricted to 1st-year residents, patient male gender, American Society of Anesthesiologists (ASA) physical status >II, emergency surgical case, operative duration ≥2 h, and paralytic agent use were associated with higher frequency of prolonged emergence, while sevoflurane or desflurane use was associated with lower frequency. Attending anesthesiologist handoff was not associated with longer emergence. Conclusion: Incidence of prolonged emergence from general anesthesia differed significantly among trainees, by resident training duration, and for patients with ASA >II.